(untitled) (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2024)
Atopic dermatitis, which develops mainly in childhood, is one of the most common skin diseases and is characterized by a complex pathogenesis affecting all organs and systems. Over the past 40 years, there has been a steady upward trend in the number of patients with atopic dermatitis all over the world, often leading to limitation of life and social functions from childhood. According to a number of authors, there is a relationship between the incidence of AD and regional environmental conditions. The influence of adverse environmental influences on the human body is due to rapid, often irrational industrialization and chemicalization, which create conditions for the accumulation of toxic substances in the external environment. The establishment of sanitary standards for the content of xenobiotics inhibits the process of degradation of the external environment, but these standards are not always and everywhere implemented punctually enough.